Exploring the characteristics of healthy lifestyle campaign on social media: a case study on FIT Malaysia - Suffian Hadi Ayub; Nurzihan Hassim; Azizul Halim Yahya; Massila Hamzah; Mohd. Zamri Abu Bakar (Penerbit Universiti Kebangsaan Malaysia, 2019)
Through the establishment of FIT Malaysia, the Malaysian Ministry of Youth and Sports (MOYS) aimed to ensure the adoption of healthy lifestyles by all Malaysians particularly youth, with initiatives to provide a variety of sports and fitness activities. This paper discusses the characteristics of the healthy lifestyle campaign by MOYS in spearheading the promotion of healthy living among youth after joining the social media bandwagon, with consideration of the time spent online by this targeted community. The study is significant to ensure that MOYS not only organises, but most importantly, utilises the most appropriate means in reaching the intended youth audiences. Through in-depth interviews with policy makers and implementers at MOYS, it was discovered that the characteristics of campaign management were not in line with social media characteristics and this has resulted in the superficial understandings of the success rate of promoting FIT Malaysia in Facebook and Twitter. This further highlighted the needs for the stakeholders to possess holistic knowledge on the social media realm as well as appropriate tools and sufficient budget to implement healthy lifestyle campaigns on social media. From this perspective, the paper provides in-depth discussions of health promotion from two aspects; the characteristics of campaign and how it can be synthesised with social media characteristics to reach out to youth and their healthy lifestyle in Malaysia through social media.